Development of land-based Mobile Mapping System (MMS) using GPS and close range photogrametry technique - Ses, Sahrum; Ahmad, Anuar; Wong, Tony Chee Siang (2004)
The last two decades have shown an increasing trend in use of GPS technology in several applications in Malaysia which including land vehicles and automated car navigation, GPS-equipped KLIA limousines, land and marine survey job which currently applied in private sector and DSMM (Department of Survey and Mapping Malaysia), deformation monitoring, etc.This research is concentrate on the geo-referencing the geographic and topography features and update a GIS (Geographic Information System) map using a consumer digital camera and GPS positioning technique. The GPS provided the position of the camera and the images from the camera are used to determine the positions of the objects.